Evaluating Antibiotic Treatment Guideline Adherence to Ongoing Antibiotic Stewardship in a Tertiary Care Setting: A Retrospective Observational Study - Suman Pant; Andrew Corwin; Prabhat Adhikari; Subhash Prasad Acharya; Upasana Acharya; Sashi Silwal; Pratima Dawadi; Anil Poudyal; Vibhu Paudyal; Adisak Bhumiratana (Canadian Journal of Infectious Diseases and Medical Microbiology)
Antimicrobial resistance (AMR) is widely regarded as an increasing threat to global public health. Antibiotic treatment guidelines have been increasingly recognized as an effective tool to guide appropriate prescriptions and help curtail antibiotic resistance. The present study aimed to assess physician’s adherence to hospital antibiotic treatment guideline recommendations in Nepal and determine predictive variables with a significant association. This was a retrospective, monocentric observational review to investigate the adherence to endorsed guidelines using the medical records of adults admitted to the hospital with a diagnosis of urinary tract infection (UTI), pneumonia, or skin and soft tissue infection (SSTI) from January 2018 to December 2019. Of the 2,077 medical records that were reviewed (954 UTI, 754 pneumonia, and 369 SSTI), 354 (17%) met the study inclusion criteria, which included 87 UTI, 180 pneumonia, and 87 SSTI patients. Among eligible patients with antibiotic prescriptions, the following were adherent to guideline recommendations: 33 (37.9%) UTI, 78 (43.3%) pneumonia, and 23 (26.4%) SSTI. The overall extent of adherence to hospital antibiotic treatment guidelines for the use of antibiotics among adult inpatients diagnosed with these common infections was 37.9%. Patients who received ceftriaxone (OR = 2.09, 95% CI = 1.18–3.71, p=0.012) and levofloxacin (OR = 4.63, 95% CI = 1.30–16.53, p=0.018) had significantly higher adherence to treatment guidelines. This study revealed a low adherence rate despite the availability of updated guidelines for antibiotic prescriptions. The findings confer an urgent need to confront antibiotic prescription patterns in such tertiary care centers for tailored interventions to improve adherence to antibiotic guidelines.